"Race" and "racism" in contemporary Africa-China relations research: approaches, controversies and reflections. Issue 3 (2nd July 2020) - castillo, Roberto
ABSTRACT: Over the last five years, as Africa-China relations have moved beyond the honeymoon period and into a more complex stage, a number of incidents have exploded into global controversies about "race, " "racism" and racial hierarchies. Given this context, research on "race" and "racism" in Africa-China relations has been scarce and fraught with methodological issues and challenges. In this article, I first provide a critical analysis of the ways in which the existing body of Africa-China relations knowledge engages with the analytical categories of "race" and "racism." After that, following Monson and Lan, who have both argued for the need of a "triangulation" to better understand "racialisation processes" in the relationship, I introduce the notion of "multiple triangulations" to both analyse these processes and to distance the discussion from Euro-American binaries and dichotomies around "race" and "racism." This is followed by a brief discussion on one of the most recent controversies relating to "race" and "racism" in Afro-Chinese mediascapes. Towards the end of the article, I reflect on the most common methodological issues and challenges in the research on Afro-Chinese encounters. Finally, I discuss the need to develop a global (post-imperial) vocabulary of "race" and "racism, " and indicate what may be the early steps towards doing so.